The Use of Origami in Teaching Writing Procedure text of the Second Grade at SMA Muhammadiyah Mataram - Muhammad Fauzi Bafadal (Linguistics and ELT Journal, 2017)
Origami is a kind of method for teaching language through dialogues whichstresses on the students’ habit formation by repetition, memorizing grammatical structures through substitutions, singular-plural and tense transformations etc, using the target language and the culture where the language is spoken. The objective of this research was to find out the effect of Origami in teaching writing procedure text. Method design this research was a true-experimental method. The population of this research was the second year students of SMA Muhammadiyah Mataram in Academic year 2016/2017. This study the writer took all population as the samples that consisted of 38 students. Because the population less than 100, they divided into two classes, namely experimental class 21 and control class 17. The writer collected the data using the testing method pre and post-test. According to Hughes rubric and t-test formula theory. The result of this research showed that the mean score of experimental group 9.5 and the mean score of control group 2.9. Based on t-test it showed that t- value 11.9 and after consulting to t-table, the t-value was higher than t- table. To conclude origami teaching and learning is more effective to improve students’ writing procedure text, this can be seen from the results of test score, it shows that the experimental class which was given treatment using origami teaching and learning got a higher score than control class without taught by used origami teaching and learning method. Besides the origami could improve the students’ motivation, the origami could attract the students’ attention, the origami help the students to memorize the vocabulary and the origami make the teaching and learning activities interesting. Presentation in which the writer presented the materials by using origami as media the students clearly and easily to understand. The writer concluded that Origami can warn up the student that was done to make students interested in learning writing procedure text and has a positive effect in teaching writing procedure text.